PENGARUH KETERAMPILAN MENGAJAR GURU DAN PARTISIPASI SISWA TERHADAP HASIL BELAJAR DASAR PROGRAM KEAHLIAN AKUNTANSI DASAR KELAS X PROGRAM KEAHLIAN AKUNTANSI SMK MUHAMMADIYAH 2 PEKANBARU - Lily Marsita; Sumarno Sumarno; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of teacher teaching skills and student participation on learning outcomes subjects Basic Accounting class X Accounting Expertise Program SMK Muhammadiyah 2 Pekanbaru. The population in this study is the students of class X Accounting Expertise Program which amounted to 99 people, the sample of this study is all students of class X Accounting Expertise Program. Data analysis method used is path analysis. The results of this study indicate that teachers' teaching skills have a positive and significant effect on student participation. Teacher's teaching skills have no significant effect on learning outcomes. Student participation has a significant effect on learning outcomes. Path analysis results obtained that the teacher's teaching skills have a direct effect on participation. Teacher's teaching skills have a direct effect on learning outcomes but have no direct effect. Student participation has a direct effect on learning outcomes.Key Words: Teacher’s Teaching Skill, Student Participation, Learning Outcomes